SEKS I PRZEMOC MAŁŻEŃSTWO W TRAGEDIACH EURYPIDESA - Spieralska, Beata (Colloquia Litteraria, 2009)
Sex and violence. Marriage in Euripides’ tragedies In ancient Athens, marriage was an event which from today’s perspective is linked with the notion of violence, even if the then living people would not have defined it in this way. From their perspective, it was obvious that the woman who was getting married was not the subject of the marital contract. Euripides tragedies, far from being a manifesto in the defence of women’s fate (it would be a complete anachronism to ascribe such motivations to the dramatist) show very frequently, however, women as victims of male disloyalty. Such heroines as Iphigenia, Alcestis or Medea appear to be more faithful to the marital contract than their husbands. To a modern reader, they may constitute a source of knowledge on the ancient Athenian institution of marriage. At the same time we have to keep in mind that caution should be exercised: tragedy is not an historiographic work, but primarily a literary fiction, set in reality, but also going beyond it. What can be, to some extent, an historical source is simultaneously – and maybe even more – an artistic creation. It allows us not only to learn about the reality of the epoch, but also admire the art with which the artist undertakes vital social issues.